Leber congenital amaurosis as an initial manifestation in a Chinese patient with thiamine‐responsive megaloblastic anemia syndrome. Issue 3 (25th November 2021) - Wu, Shijing; Yuan, Zhisheng; Sun, Zixi; Yao, Fengxia; Sui, Ruifang
Abstract: Thiamine‐responsive megaloblastic anemia syndrome (TRMA) is an autosomal recessive disorder, inherited by the defective SLC19A2 gene that encodes a high‐affinity thiamine transporter (THTR‐1). TRMA is characterized by the occurrence of classical triad manifestations including megaloblastic anemia, diabetes mellitus, and sensorineural deafness. In addition to the systemic manifestations, ophthalmic features can be present and include retinitis pigmentosa, optic atrophy, cone‐rod dystrophy, maculopathy, and Leber congenital amaurosis. Here we report a 6‐year‐old boy presenting severe early‐onset retinal dystrophy with the initial diagnosis of Leber congenital amaurosis, which followed for 12 years. Diabetes mellitus occurred 3 years after vision problem. Eosinophilic granuloma of the left scapula was confirmed at 13 years old. Whole‐exome sequencing was performed to identify two novel compound heterozygous variants c.725dupC (p.Ala243Serfs*3) and c.121G>A (p.Gly41Ser) in SLC19A2 gene (NM_006996.3). Oral thiamine supplementation treatment was initiated at 13 years. This case demonstrates Leber congenital amaurosis can present as the first clinical feature before systemic manifestations. Phenotypic variety should be aware and multidisciplinary teamwork and regular follow‐up are important for TRMA patient care.